Corak Pemikiran Nurcholish Madjid dalam Bingkai Politik Kebangsaan di Indonesia: Nurcholish Madjid's Thought Patterns in the Framework of National Politics in Indonesia - Hidayatulloh, Taufik; Muna, Izzul (Undiksha, 2024)
The process of seeking meaning within oneself is a deep and often complex journey involving various psychological, emotional, and philosophical aspects. This includes when an individual interprets themselves as a volunteer. This study explores the experiences and life meanings of social volunteers in Bali through the lens of Jean-Paul Sartre's existentialism. The data for this research was collected through in-depth interviews with three informants, selected using snowball sampling techniques. The interview results were then analyzed using Sartre's existentialist perspective. The findings, related to the principle that